2020
DOI: 10.1088/1742-6596/1611/1/012054
|View full text |Cite
|
Sign up to set email alerts
|

The impact of trauma of the mucous membrane of the nasal septum in rats on behavioral responses and changes in the balance of the autonomic nervous system (pilot study)

Abstract: The nasal cavity surgery are usually traumatic surgery. Septoplasty leads to reactive inflammation, edema and hypoxemia. In the present study, we study the response of the autonomic nervous system (ANS), its role in changing behavioral reactions, as well as possible mechanisms of impairment of cognitive and adaptive reactions in rats after trauma to the nasal septum mucosa. The nasal septum mucosa was scarified in 10 adult mongrel male rats. The day before surgery and 2 days after surgery animals were tested i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…The close connection of this HRV component with metabolism is confirmed by the relationship between diurnal changes in the concentration of the adipocyte hormone leptin in blood serum and diurnal changes in the VLF component of HRV [19]. The obtained difference between the groups can be explained by the fact that under conditions of complete deprivation of the olfactory analyzer, rats develop an anxiety state, and motor activity increases, since the olfactory analyzer in these animals is the leading one in cognition of the environment [8].…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…The close connection of this HRV component with metabolism is confirmed by the relationship between diurnal changes in the concentration of the adipocyte hormone leptin in blood serum and diurnal changes in the VLF component of HRV [19]. The obtained difference between the groups can be explained by the fact that under conditions of complete deprivation of the olfactory analyzer, rats develop an anxiety state, and motor activity increases, since the olfactory analyzer in these animals is the leading one in cognition of the environment [8].…”
Section: Discussionmentioning
confidence: 69%
“…Traditionally, frequency domain analysis of HRV reveals two or more peaks, a lower frequency (<0.15 Hz) and a higher frequency peak (>0.15 Hz), which are generally correlated with sympathetic and parasympathetic effects on cardiac activity, respectively. The decrease in HF compared to LF and the increase in VLF, which are observed simultaneously with changes in the behavior of rats under stress [8,13], can be explained by the effect of post-surgical inflammation. High LF values in the bulbectomy group indicate a decrease in the activity of the SNS in the regulation of cardiac activity against the background of deprivation of the central part of the olfactory analyzer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological changes in the hippocamp are confirmed by our previous studies, which showed that septoplasty simulation in rats provokes the development of many stress reactions [34] and even a breakdown in adaptation [35]: an increase in the number of dark neurons [36], the expression of the p53 protein [3], a significant release of corticosterone into the blood plasma [37], and an increase in degranulation of mast cells [38], disturbances in the balance of the autonomic nervous system [37,39,40], changes in behavior when testing rats in an open field [9], the appearance of anxiety and a depressive-like state [37,[41][42][43].…”
Section: Discussionmentioning
confidence: 99%
“…Morphological changes in the hippocamp are confirmed by our previous studies, which showed that septoplasty simulation in rats provokes the development of many stress reactions [34] and even a breakdown in adaptation [35]: an increase in the number of dark neurons [36], the expression of the p53 protein [3], a significant release of corticosterone into the blood plasma [37], and an increase in degranulation of mast cells [38], disturbances in the balance of the autonomic nervous system [39,40], changes in behavior when testing rats in an open field [9], the appearance of anxiety and a depressivelike state [41].…”
Section: Discussionmentioning
confidence: 99%